Regulation of Swarming Motility and flhDC(Sm) Expression by RssAB Signaling in Serratia marcescens - Soo, Po-Chi (American Society for Microbiology (ASM), 2008)
Serratia marcescens cells swarm at 30°C but not at 37°C, and the underlying mechanism is not characterized. Our previous studies had shown that a temperature upshift from 30 to 37°C reduced the expression levels of flhDC(Sm) and hag(Sm) in S. marcescens CH-1. Mutation in rssA or rssB, cognate genes that comprise a two-component system, also resulted in precocious swarming phenotypes at 37°C. To further characterize the underlying mechanism, in the present study, we report that expression of flhDC(Sm) and synthesis of flagella are significantly increased in the rssA mutant strain at 37°C. Primer extension analysis for determination of the transcriptional start site(s) of flhDC(Sm) revealed two transcriptional start sites, P1 and P2, in S. marcescens CH-1. Characterization of the phosphorylated RssB (RssB∼P) binding site by an electrophoretic mobility shift assay showed direct interaction of RssB∼P, but not unphosphorylated RssB [RssB(D51E)], with the P2 promoter region. A DNase I footprinting assay using a capillary electrophoresis approach further determined that the RssB∼P binding site is located between base pair positions −341 and −364 from the translation start codon ATG in the flhDC(Sm) promoter region. The binding site overlaps with the P2 “−35” promoter region. A modified chromatin immunoprecipitation assay was subsequently performed to confirm that RssB∼P binds to the flhDC(Sm) promoter region in vivo. In conclusion, our results indicated that activated RssA-RssB signaling directly inhibits flhDC(Sm) promoter activity at 37°C. This inhibitory effect was comparatively alleviated at 30°C. This finding might explain, at least in part, the phenomenon of inhibition of S. marcescens swarming at 37°C.